Dinamika Identitas Perempuan melalui Praktik Rias di Jepang, Korea, dan Tiongkok - Lintang Azzikra Gantari; Maria Krisnawati; Anik Maghfiroh; Taqiya Cantika As Salma; Ega Rahmania Putri; Afrilia Ishmatul Khawa (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2025)
This article examines the evolution of the concept of femininity in East Asian makeup culture by tracing changes in style, function, and social meaning from traditional periods to the modern era. The study focuses on makeup practices in China, Japan, and Korea, which possess distinct cultural and historical backgrounds yet similarly demonstrate dynamic developments of femininity through visual expression. The research employs a literature review using a qualitative approach, complemented by an analysis of beauty trends emerging in each country. The findings indicate that facial makeup functions not merely as an aesthetic practice but also as a medium for representing personal identity, social status, gender roles, and prevailing cultural values within society. The transformation of makeup practices is influenced by various factors, including local traditional heritage, processes of modernization, changes in women’s roles, and globalization, which introduces new beauty standards. Nevertheless, traditional elements continue to be preserved and adapted, forming distinctive regional characteristics. Overall, this study emphasizes that the concept of femininity in East Asian makeup culture is dynamic and contextual, continually adapting to social change while remaining deeply rooted in longstanding cultural values.